Perancangan Sistem Informasi Akuntansi Penjualan Menggunakan Standar Akuntansi EMKM - Najla Najla; S Supriyati; Deshinta Arrova Dewi (Labkat Press KA FTIK UNIKOM, 2022)
This study intends to design a sales accounting information system for UMKM Toko Utara Game. The purpose of this study is to design a sales information system with EMKM standards at Toko Utara Game that can be implemented as one of the human error risk management that might occur if the system is run conventionally and not computerized. The research method used in this study is a descriptive research method, in which the author analyzes and describes events that occur in the present with the intention of overcoming problems that occur at Toko Utara Game. The types of data used in this research are primary data and secondary data. Data collection techniques used in this study were interviews, observation and literature studies. The results of interviews and observations are used as primary data and the results of literature studies are used as secondary data. The system development methodology used in this study is the prototyping method with an object-oriented system design method using UML (Unified Modeling Language). The system design made in this study is a Use Case Diagram, an Activity Diagram, and uses an Entity Relationship Diagram (ERD). At the stage of creating the program code, researchers used the Java and MYSQL programming languages which were poured into the NetBeans IDE8.1 software using XAMPP as a web server. The result of this implementation is the design of a web-based sales application so that Toko Utara Game sales management can be computerized properly.